2020
DOI: 10.1002/aoc.5729
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, spectroscopic, electrochemical characterization, density functional theory (DFT), time dependent density functional theory (TD‐DFT), and antibacterial studies of some Co(II), Ni(II), and Cu(II) chelates of (E)‐4‐(1,5‐dimethyl‐3‐oxo‐2‐phenyl‐2,3‐dihydro‐1H‐pyrazol‐4‐yl)‐1‐(3‐hydroxynaphthalen‐2‐yl)methylene) thiosemicarbazide Schiff base ligand

Abstract: In this study, mononuclear Co(II), Ni(II), and Cu(II) chelates of the potentially tridentate O, N, S donor ligand (E)-4-(1,5-dimethyl-3-oxo-2-phenyl-2,3-dihydro-1H-pyrazol-4-yl)-1-(3-hydroxynaphthalen-2-yl)methylene) thiosemicarbazide (H 2 L) were synthesized and characterized by elemental analyses, conductivity measurements, Fourier transform infrared spectroscopy, UV-visible spectroscopy, magnetic susceptibility, electron spin resonance (ESR) spectral analysis, thermal thermogravimetric analyses, cyclic volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 94 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…The electronic band gap for Eu4 (3.201 eV) was found to be high in comparison with that for DD (2.989 eV). [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
“…The electronic band gap for Eu4 (3.201 eV) was found to be high in comparison with that for DD (2.989 eV). [ 44 ]…”
Section: Resultsmentioning
confidence: 99%
“…The negatively charged surface groups (carboxyl or phosphate), which are present in the E. coli cell wall, can form bonds with the metal, released by the CoMoO 4 ·1.03H 2 O during the process called biosorption, destroying the integrity of the cell membrane and causing protein clotting [ 51 ]. It is also known that the coordination and redox chemical properties of cobalt can lead to its non-specific binding to various proteins, displacement of other metals (usually iron) from their natural binding sites, and the generation of free radicals [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the metal ion binding to biomolecules such as proteins, enzymes, and peptidoglycans present in the cell wall, El-Shaafaf et al [ 51 ] showed that metal can induce bacterial death by another route, in which it intercalates with phosphorus (compositional element is the teichoic acids that make up the cell wall of S. aureus ) elements in bacterial DNA, preventing the replication and expression of the ribosomal subunit protein and other cellular proteins. Consequently, the data that are presented in Table 5 in relation to the MIC of the analyzed systems infer that the metal performed this route more efficiently when they penetrated the cell wall of S. aureus .…”
Section: Resultsmentioning
confidence: 99%
“…The metal complexes were prepared according to the general procedure by mixing equal amounts (0.02 mol) [34][35][36][37] of hot ethanol solution of the ligand (HL) with the same ratio of metal salt (M:L = 1:1 molar ratio). The reaction mixture was refluxed under constant magnetic stirring for 12 h at 80 C. The resulting product was filtered and washed several times with ethanol.…”
Section: Synthesis Of the Metal Complexesmentioning
confidence: 99%